Benefits of Education for the Nation's Next Generation - Anita Candra Dewi; Haikal; Muh. Luthfi; Selvira; Priska Febriona Tonapa; Khaerul Aksanul Muslimin (MultiTech Publisher, 2023)
Education is a learning process, knowledge, or abilities and skills that are seen from each person's habits, education is really needed to support knowledge, training, or research. In UUD number 20 of 2003, the National education system in education also contains educational objectives which are basically a forum or means for developing personality and the potential to increase knowledge. Education functions to form a good self from abilities, skills, ethics and morals to make a better person. Education is a means to equip oneself to face the world of society because the world is not only about knowledge but includes social, ethical and civilized aspects. Of course, education has benefits for those who attend education, because it will have a great influence on both themselves and their environment, which will be examined more clearly in the next discussion.